2022
DOI: 10.17762/ijcnis.v10i1.3072
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive FLV Steganography Approach Using Simulated Annealing

Abstract: Steganography is not only the art of hiding secret messages in cover media but also a process of communication and secure data transfer. Secret messages can be sent over the Internet with security by using several steganography techniques, but all of them present challenges in steganalysis. This study proposes a new secure technique called flash video (FLV) file steganography that keeps the frame video quality and is difficult to detect. The technique can hide any type of secret message inside a given FLV file… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…On the other hand, the algorithm still weak to handle by statistical analysis, since it uses sequential hiding mechanism, also the data are being hidden without any type of encryption which makes it very easy to be extracted. Other researchers reduce the noise on the cover-image by hiding one bit per pixel [4] and maintained that LSB achieves its objective by altering the coloring scheme of an image, thus making it difficult for the human eye to discern the content and found that LSB does not distort the image. Yang, C., et al (2008 ) [25] modified LSB technique known as adaptive data hiding, whereby it works on the principle of hiding information within the edges of an image.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, the algorithm still weak to handle by statistical analysis, since it uses sequential hiding mechanism, also the data are being hidden without any type of encryption which makes it very easy to be extracted. Other researchers reduce the noise on the cover-image by hiding one bit per pixel [4] and maintained that LSB achieves its objective by altering the coloring scheme of an image, thus making it difficult for the human eye to discern the content and found that LSB does not distort the image. Yang, C., et al (2008 ) [25] modified LSB technique known as adaptive data hiding, whereby it works on the principle of hiding information within the edges of an image.…”
Section: Related Workmentioning
confidence: 99%
“…Bawaneh developed a random LSB image steganography system (LCG) by using a linear congruent generator (LCG) [3]. The system within the RGB color picture inserted the hidden message in random positions which LCG developed.…”
Section: Related Workmentioning
confidence: 99%
“…Today in the digital world, various types of files may be used as cover of secret data, like, audio, text, image, or video. The steganography methods could be classified as injection, substitution, and distortion or generation due to variations in the procedures carried out to do the embedding process [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clustering technique of the color image is used to protect the embedded steganography from attacks. Bawaneh et al in [18] proposed a secure technique called flash video file steganography that saves the quality of video frames. Their proposed technique is able to hide different types of secret message inside the cover image.…”
Section: Proposed Algorithmmentioning
confidence: 99%